Selective Disruption of Mitochondrial Thiol Redox State in Cells and In Vivo. Issue 3 (21st March 2019) - Booty, Lee M.; Gawel, Justyna M.; Cvetko, Filip; Caldwell, Stuart T.; Hall, Andrew R.; Mulvey, John F.; James, Andrew M.; Hinchy, Elizabeth C.; Prime, Tracy A.; Arndt, Sabine; Beninca, Cristiane; Bright, Thomas P.; et al.
Summary: Mitochondrial glutathione (GSH) and thioredoxin (Trx) systems function independently of the rest of the cell. While maintenance of mitochondrial thiol redox state is thought vital for cell survival, this was not testable due to the difficulty of manipulating the organelle's thiol systems independently of those in other cell compartments. To overcome this constraint we modified the glutathione S-transferase substrate and Trx reductase (TrxR) inhibitor, 1-chloro-2, 4-dinitrobenzene (CDNB) by conjugation to the mitochondria-targeting triphenylphosphonium cation. The result, MitoCDNB, is taken up by mitochondria where it selectively depletes the mitochondrial GSH pool, catalyzed by glutathione S-transferases, and directly inhibits mitochondrial TrxR2 and peroxiredoxin 3, a peroxidase. Importantly, MitoCDNB inactivates mitochondrial thiol redox homeostasis in isolated cells and in vivo, without affecting that of the cytosol. Consequently, MitoCDNB enables assessment of the biomedical importance of mitochondrial thiol homeostasis in reactive oxygen species production, organelle dynamics, redox signaling, and cell death in cells and in vivo . Graphical Abstract: Highlights: MitoCDNB is a mitochondria-targeted molecule that disrupts thiol redox state The CDNB moiety depletes glutathione and inhibits key thiol redox enzymes MitoCDNB selectively disrupts mitochondrial thiol redox state in cells and in vivo MitoCDNB extends methods available to investigate mitochondrial thiol redox state Abstract : It has been difficult to selectively disrupt mitochondrial redox state, independently of that in the rest of the cell. Here, Booty et al. introduce MitoCDNB to deplete mitochondrial glutathione and selectively inhibit key enzymatic components of mitochondrial thiol redox status in cells and in vivo .